Children's encyclopedia : the book that explains everything! - Davey,Lizzie (New York DK Publishing, 2022)
"This book of essential knowledge will inspire young minds to learn about big topics, through fun facts and beautiful illustrations. DK Children's Encyclopedia is a must-have resource for every kid's bookshelf, covering over 250 topics all in one place! This is the ultimate knowledge book for children aged 7-9, written and designed by a team of experts, checked by educational consultants, and edited for appropriate reading age. Children can enjoy learning all about big topics from Myths and Legends, to Viruses and Space Exploration, to keep curious minds active and engaged."
Keywords: Enclopedia